Demographic Profile of Patients with Dengue Fever Presented in a Tertiary Care Hospital of Bangladesh - Yasmin, Farzana; Uddin Ahmed, Md Ashraf (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Dengue is an important tropical infection caused by an arbovirus having four serotypes (DENV-1, DENV-2, DENV-3, DENV-4) transmitted through the bite of infected female Aedes mosquito. Dengue is a challenging disease with multisystemic, varied, atypical, and sometimes life-threatening presentations. It presents as varied clinical spectrum of dengue fever (DF), dengue hemorrhagic fever (DHF), dengue shock syndrome (DSS) and expanded dengue syndrome (EDS) with atypical presentations, thus posing a diagnostic dilemma. Each year, thousands of dengue infections are reported and there are several outbreaks of dengue in several countries including Bangladesh and this imply the global importance of this infection. The objectives of this study was to determine the sociodemographic variables of patient suffering from DF during an epidemic outbreak. Methods: This hospital review analyzed the hospital records of DF cases of BIRDEM General Hospital, Dhaka from June 2019 to December 2019. Patients with suspected dengue fever attending at the outdoor/emergency or admitted indoor were taken as study subjects. Data were collected from hospital records. Study protocol was approved by the Institutional Review Board. All the relevant data regarding history and examination findings of the patients, the laboratory reports were collected. Statistical package for social science (SPSS) version 22, was used for data entry and statistical analysis. Results: Total 292 dengue patients were enrolled in this study. Mean age of all patient was 35.63±15.22 years (11-85 year) with male predominance (54.8%). Maximum patients were from urban residence (83.9%), non-smoker (73.6%), had active lifestyle (63.4%) and normal body mass index (68.5%). Overall, 65.1% patients had no comorbidity and 89.4% had no concurrent acute illness. Conclusion: Although the results of this study cannot be generalized to other cities of Bangladesh, our findings will allow public health agencies in Bangladesh to concentrate their efforts to battle against dengue. J Bangladesh Coll Phys Surg 2023; 41: 63-68